Commodity control : a study of primary products - Yates, P. Lamartine; Fabian Society (Great Britain) (London : J. Cape, 1943)
These studies on the wealth accumulation and men decay.
"First published 1943."
A publication of the Fabian society summarizing studies undertaken by the author and other members of the society. cf. Pref.
Includes bibliographical footnotes and index.
uaa 22/01/2019
Loans
Keywords: Commercial products; Commercial policy